2008
DOI: 10.1002/eji.200737936
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial cells modify immune responses by inducing an anti‐inflammatory microenvironment

Abstract: The upper airways are prone to contact with pathogenic as well as non-pathogenic microbes, therefore immune recognition principles have to be tightly controlled. Here we show that human BEAS-2B bronchial epithelial cells inhibited secretion of the proinflammatory cytokines TNF-a and IL-12 by monocytes, macrophages and dendritic cells. This inhibitory effect could be transferred by supernatant of resting BEAS-2B cells and was also observed when primary murine tracheal epithelial cells were prepared. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 39 publications
(63 reference statements)
8
104
1
Order By: Relevance
“…10 Although ECs were found to induce Treg expansion, 13,14,40 restrained CD4 1 T-cell expansion in response to Aspergillus, 19 and produce IL-10 (this study), the therapeutic effects of kynurenines will undoubtedly cover IDO deficiency also in DCs. As a matter of fact, the highly polarized Th2/Th17 responses seen in Trif 2/2 mice are immunological features compatible with the functional program activated in lung DCs by the TRIF pathway.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…10 Although ECs were found to induce Treg expansion, 13,14,40 restrained CD4 1 T-cell expansion in response to Aspergillus, 19 and produce IL-10 (this study), the therapeutic effects of kynurenines will undoubtedly cover IDO deficiency also in DCs. As a matter of fact, the highly polarized Th2/Th17 responses seen in Trif 2/2 mice are immunological features compatible with the functional program activated in lung DCs by the TRIF pathway.…”
Section: Discussionmentioning
confidence: 69%
“…[10][11][12] No longer considered innocent bystanders, 13 airway epithelial cells (ECs) are central participants in innate and adaptive immune responses as well as mucosal inflammation and allergy. 14 Through the activation of Toll-like receptors (TLRs) by endogenous and exogenous ligands, ECs may play a central role in determining the balance between a state of 'mucosal homeostasis', as is required for optimal organ function, and 'mucosal injury', leading to mucosal inflammation and barrier breakdown. 13 Recent evidence indicated that ECs may also contribute to immunity to respiratory pathogens.…”
Section: Dendritic Cells (Dcs) Orchestrate the Adaptive Immune Responmentioning
confidence: 99%
“…Transcriptional profiling of AMs in smokers has indicated a marked macrophage reprogramming in smokers (3,4), with suppression of inflammatory genes associated with classical M1-related inflammatory/immune genes and induction of genes associated with various M2-polarization programs relevant to tissue remodeling and immunoregulation, findings that are consistent with reduced innate immune responses and increased susceptibility to respiratory infections in smokers or CS-exposed individuals (2,5). Actions of CS on airway epithelial cells affect their production of inflammatory or host defense mediators (6)(7)(8)(9) and their interactions with DCs (10,11). Furthermore, direct actions of CS on DCs may affect DC maturation (12) and polarize T helper (Th) 2 immune responses (13,14).…”
mentioning
confidence: 99%
“…Furthermore, the results from our study also demonstrate that soluble components secreted by 3D organotypic models are responsible for the enhanced production of CCL18 in DC. Although, differential expression of cytokines and chemokines by DC in response to monolayer of lung epithelial cells has been observed (26,29), the effect of 3D tissue models on DC function is limited. Therefore, we investigated whether there are differences between the 3D organotypic model, AE epithelial cells, AE fibroblasts, or submerged monolayer culture of epithelial cells and fibroblasts in terms of altering the capacity of DC to produce CCL18.…”
Section: Discussionmentioning
confidence: 99%